Bis-isatin derivatives: design, synthesis, and biological activity evaluation as potent dimeric DJ-1 inhibitors - Chen Xiao-bing; Zhu Hai-ying; Bao Kun; Jiang Li; Zhu Hong; Ying Mei-dan; He Qiao-jun; Yang Bo; Sheng Rong; Cao Ji (Acta Pharmacologica Sinica; Vol 42, No 7 (July 2021): Acta Pharmacologica Sinica, 2021)
The PARK7 gene (encode DJ-1 protein) was first discovered as an oncogene and later found to be a causative gene for autosomal recessive early onset Parkinson’s disease. DJ-1 has been proposed as a potential therapeutic anticancer target due to its pivotal role in tumorigenesis and cancer progression. Based on the homodimer structure of DJ-1, a series of bis-isatin derivatives with different length linkers were designed, synthesized, and evaluated as dimeric inhibitors targeting DJ-1 homodimer. Among them, DM10 with alkylene chain of C10 displayed the most potent inhibitory activity against DJ-1 deglycase. We further demonstrated that DM10 bound covalently to the homodimer of DJ-1. In human cancer cell lines H1299, MDA-MB-231, BEL7402, and 786-O, DM10 (2.5–20 μM) inhibited the cell growth in a concentration-dependent manner showing better anticancer effects compared with the positive control drug STK793590. In nude mice bearing H1299 cell xenograft, intratumor injection of DM10 (15 mg/kg) produced significantly potent tumor growth inhibition when compared with that caused by STK793590 (30 mg/kg). Moreover, we found that DM10 could significantly enhance N-(4-hydroxyphenyl)retinamide-based apoptosis and erastin-based ferroptosis in H1299 cells. In conclusion, DM10 is identified as a potent inhibitor targeting DJ-1 homodimer with the potential as sensitizing agent for other anticancer drugs, which might provide synergistical therapeutic option for cancer treatment.